The Protective Effect of Sulforaphane on ER-induced Apoptosis and Inflammation in Necrotizing Enterocolitis Mice - Wang, Xinhong; Mi, Yanhong; Xiong, Xiaoyu; Bao, Zhongkun (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Necrotizing enterocolitis (NEC) is a neonatal intestinal necrotizing disease caused by various factors in newborns. Sulforaphane (SFN) has a strong anti-inflammatory ability and a certain protective effect on intestinal diseases. Objective: NEC is a common developed gastrointestinal exigency in an untimely baby. SFN is a naturally originated isothiocyanate that has beneficial effects on the intestinal system.The purpose of this study is to study the protective effect of SFN on endoplasmic reticulum stress (ERS)-related NEC. Methods: The newborn mice were randomly divided into control (n = 15), NEC (n = 20), and NEC+SFN (n = 18) groups. Mice in NEC and SFN+NEC groups were injected with 0.1 μl normal saline or 20 mg/kg/d SFN, respectively. After that, the weight and survival of the mice were recorded every day. Then the mice were sacrificed after 96 h of modeling; ileum tissue and blood samples were collected for qPCR, Western blot, ELISA, HE staining, TUNEL staining, and immunohistochemistry assays. Results: SFN significantly inhibited the mRNA expression of BIP, CHOP, IL-1β and IL-6, and protein expression of Bax, Caspase-3, Caspase-9 and CHOP, and promoted the expression of Bcl-2 in ER-induced NEC mice intestinal tissues (P<0.01). Meanwhile, SFN could suppress the serum levels of IL-8, IL-10, IL-6, TNF-α, and IL-1β, and positive expression of TLR4 and NF-ΚB (P<0.01), and promote the serum levels of IL-10. HE staining showed that SFN alleviated the NEC intestinal tissue injury, and TUNNEL staining showed that SFN could reduce the rate of NEC apoptotic cells (P<0.01). Moreover, SFN treatment improved the body weight and survival rate in NEC mice. Conclusion: SFN could effectively protect against ERS-induced inflammation and apoptosis in NEC mice.
Keywords: endoplasmic reticulum